2018
DOI: 10.1093/cercor/bhy048
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles for the Cerebellum, Angular Gyrus, and Middle Temporal Gyrus in Action–Feedback Monitoring

Abstract: Action-feedback monitoring is essential to ensure meaningful interactions with the external world. This process involves generating efference copy-based sensory predictions and comparing these with the actual action-feedback. As neural correlates of comparator processes, previous fMRI studies have provided heterogeneous results, including the cerebellum, angular and middle temporal gyrus. However, these studies usually comprised only self-generated actions. Therefore, they might have induced not only action-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 62 publications
4
74
2
1
Order By: Relevance
“…First, regions of the bilateral anterior and posterior cerebellum, including lobules IV-V and IX, were found to be significantly engaged for trials in which a delay was detected versus not detected during self-generated movements. This is in line with the notion of the cerebellum as a state estimator, modulating predicted sensory consequences of motor commands and providing error signal for the unpredicted consequences of these commands (Blakemore & Frith, 2003;Blakemore et al, 2001;Leube et al, 2003;Miall, Weir, Wolpert, & Stein, 1993;Miall et al, 2007;van Kemenade et al, 2019;Wolpert et al, 1998). Our finding of higher involvement in the cerebellar areas for subjectively delayed trials during self-compared with externallygenerated movements not only supports the cerebellum's role as generating predictions and detecting errors during sensorimotor processing, but it also provides a subjective component to the involvement of the cerebellum in processing these discrepancies.…”
Section: Bold Suppression In Sensory Cortices During Self-generated Msupporting
confidence: 75%
See 3 more Smart Citations
“…First, regions of the bilateral anterior and posterior cerebellum, including lobules IV-V and IX, were found to be significantly engaged for trials in which a delay was detected versus not detected during self-generated movements. This is in line with the notion of the cerebellum as a state estimator, modulating predicted sensory consequences of motor commands and providing error signal for the unpredicted consequences of these commands (Blakemore & Frith, 2003;Blakemore et al, 2001;Leube et al, 2003;Miall, Weir, Wolpert, & Stein, 1993;Miall et al, 2007;van Kemenade et al, 2019;Wolpert et al, 1998). Our finding of higher involvement in the cerebellar areas for subjectively delayed trials during self-compared with externallygenerated movements not only supports the cerebellum's role as generating predictions and detecting errors during sensorimotor processing, but it also provides a subjective component to the involvement of the cerebellum in processing these discrepancies.…”
Section: Bold Suppression In Sensory Cortices During Self-generated Msupporting
confidence: 75%
“…Data from all participants was taken from a recent study by our group in which we examined contributions of different regions in action-feedback monitoring of naturalistic self-versus externally generated movements (van Kemenade et al, 2019). The experimental design and data acquisition procedures have been reported previously in van Kemenade et al 2019and restated below for the reader's convenience.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, sensitivity to alterations in the temporal aspect must rely on comparison of onset timing relations between visual and sensorimotor signals. Brain-imaging studies have shown that this is processed in parietal and cerebellar regions (Blakemore & Sirigu, 2003;Farrer, Frey, et al, 2008;Leube et al, 2003;MacDonald & Paus, 2003;Salomon, Malach, & Lamy, 2009;van Kemenade et al, 2018). However, detecting discrepancies in the spatial or anatomical aspects may require different computations, taking into account continuous action plans and somatotopic representations associated with frontal and parietal regions as well as the extrastriate body area (David et al, 2007;.…”
Section: Discussionmentioning
confidence: 99%